Isolation of Lactic Acid Bacteria from Malaysian Foods and Assessment of The Isolates for Industrial Potential - Adnan, A.F.M.; Tan, I.K.P. (2007)
Two traditional fermented food 'tapai' (fermented tapioca) and 'tempoyak' (fermented durian flesh), chilli puree and fresh goat's milk were used as sources for the isolation of lactic acid bacteria (LAB). A total of 126 isolates were obtained and by sequential screening for catalase activity and Gram-staining, 55 were determined to be LAB out of which 16 were established to be homofermentative by the gel plug test. Seven isolate's were identified by use of the API 50CHL kit and two lactobacilli strains and one lactococci strain were selected to study their growth and lactic acid production profiles in a time course experiment. The lactobacilli strains, both isolated from 'tapai', produced higher amounts of cells and lactic acid from glucose as compared to the lactococci strain isolated from fresh goat's milk. (c) 2006 Elsevier Ltd. All rights reserved.